Respuesta :
Answer:
C. 29
Step-by-step explanation:
[tex]f(x) = -3x^3 + 2x^2 +24[/tex]
• To calculate [tex]f(-1)[/tex] , we have to replace x with -1 in the definition of [tex]f(x)[/tex] , and calculate the value:
[tex]f(-1) = -3(-1)^3 + 2(-1)^2 + 24[/tex]
⇒ [tex]-3(-1) +2(1) + 24[/tex]
⇒ [tex]3 + 2 + 24[/tex]
⇒ [tex]29[/tex]
[tex]\huge\boxed{\textsf{C.}\ 29}[/tex]
We have this equation:
[tex]f(x)=-3x^3+2x^2+24[/tex]
Substitute [tex]x=-1[/tex]:
[tex]f(-1)=-3(-1)^3+2(-1)^2+24[/tex]
Simplify to find the final answer:
[tex]\begin{aligned}f(-1)&=-3(-1)+2(1)+24\\&=3+2+24\\&=5+24\\&=\boxed{29}\end{aligned}[/tex]